Developing a research agenda on exercise and physical activity for people with limb loss in Canada. Issue 25 (4th December 2022) - MacKay, Crystal; Lee, Leanna; Best, Krista; Campbell, Janet; Cimino, Stephanie R.; Cowley, Heather; Delvin, Michael; Dilkas, Steven; Landry, Mireille; Marzolini, Susan; Mayo, Amanda; Oh, Paul; et al.
Abstract: Purpose: There is a lack of high-quality evidence about the effects of exercise or physical activity interventions for adults with lower limb amputations (LLAs). A planning meeting involving stakeholders (i.e., people with LLA, community advocates, health care providers, researchers) was organized to identify key research priorities related to exercise and physical activity for people with LLAs. Methods: We used a collaborative prioritized planning process with a pre-meeting survey and 2-day virtual meeting that included: identification and prioritization of challenges or gaps; identification and consolidation of solutions; and action planning. This process integrated a modified Delphi approach, including anonymous feedback in two surveys. Results: Thirty-five stakeholders participated. Six challenges related to exercise and physical activity for people with LLA were prioritized. One solution was prioritized for each challenge. After consolidation of solutions, participants developed five research action plans for research including: developing an on-line interface; developing and evaluating peer-support programs to support physical activity; examining integration of people with LLA into cardiac rehabilitation; development and evaluation of health provider education; and determining priority outcomes related to physical activity and exercise. Conclusions: This collaborative process resulted in an action plan for amputation research and fostered collaborations to move identified priorities into action. IMPLICATIONS FOR REHABILITATION: Lower limb amputations impact mobility leading to lower levels of physical activity. There are research gaps in our understanding of the effects of exercise or physical activity interventions for adults with lower limb amputations. Through a collaborative planning process, participants prioritized research directions on physical activity and exercise for people with LLA to advance research in the field. Action plans for research focused on developing online resources, peer support, cardiac rehabilitation for people with LLA, health provider education and determining priority outcomes related to physical activity and exercise.